REGIONAL ALGORITHM OF CARE IN ST ELEVATION MYOCARDIAL INFARCTION - A. Yu. Vafin; A. S. Galyavich (Российский кардиологический журнал, 2016)
The aim of the study — to present the developed and applied algorithms of ST elevation myocardial infarction (STEMI) patients. The data analyzed on the medical care provision for STEMI in Tatarstan Republic in 2009-2015 y. Application of algorithms with considered regional specifics and resources makes to significantly decrease the values of in-hospital mortality in STEMI.